Simulation Model for Stochastic Analysis and Performance Evaluation of Condensate System of a Thermal Power Plant - Gupta, Sorabh; Tewari, PC (Bangladesh Journal of Scientific and Industrial Research, 2010)
This paper discusses the stochastic analysis and performance evaluation of condensate system of a thermal plant. These opportunities will be identified by evaluation of a simulation model to be built for the condensate system. The present system under study consists of six subsystems A, B, C, D, E, and F arranged in series with two feasible states: working and failed. After drawing transition diagram, differential equations are generated and then a probabilistic simulated simulation model using Markov approach has been developed considering some assumptions. Performance matrix for each subsystem is also developed, which provide various availability levels. On the basis of this study, performance of each subsystem of condensate system is evaluated and then maintenance decisions are made for subsystems. Key words: Transition diagram; Markov approach; Performance matrix; Maintenance decisions. DOI: 10.3329/bjsir.v44i4.4587 Bangladesh J. Sci. Ind. Res. 44(4), 387-398, 2009